2021
DOI: 10.1039/d0ce01387k
|View full text |Cite
|
Sign up to set email alerts
|

Physical stability enhancement and antimicrobial properties of a sodium ionic cocrystal with theophylline

Abstract: In the present study, we have described the synthesis and characterisation of the theophylline hydrate (Theo hydrate), cocrystal (Theo–Phen·2H2O) and hydrated sodium co-crystal of theophylline (Na–(Theo)2ClO·2H2O), where Theo = theophylline and Phen = 1,10-phenathroline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…S10, S12 and S14†) and TGA (Fig. S11, S13 and S15†), which showed that hydrates 2H-b , 28 3H-a 29 and 4H-a 25 were made using this method.…”
Section: Methodsmentioning
confidence: 86%
“…S10, S12 and S14†) and TGA (Fig. S11, S13 and S15†), which showed that hydrates 2H-b , 28 3H-a 29 and 4H-a 25 were made using this method.…”
Section: Methodsmentioning
confidence: 86%
“…2c) that contribute to a significant stabilization of this hydrated sodium cocrystal (Na–(Theo) 2 –ClO·2H 2 O), compared with the traditional hydrated cocrystal without the participation of sodium (Theo–Phen·2H 2 O). 86 Furthermore, the employment of halogen-bond synthons in cocrystal design (Fig. 2d) also successfully transformed the highly volatile liquid iodoperfluoroalkanes into crystalline materials with long-term stability.…”
Section: Cocrystal Strategy To Different Environmental Stressmentioning
confidence: 99%
“…[24][25][26] Its modulation has enabled the enhancement of the thermal stability and processability of the determined molecules through the formation of cocrystals. [27][28][29] Indeed, our group has previously studied the formation of cocrystals based on the acid⋯amide 30 and acid⋯pyridine heterosynthons 31 and the correlation of the crystal packing with their melting point values. 31 Therefore, aiming to extend our knowledge on the structure-property relationship of cocrystals focusing on the melting point, we have selected a liquid and a solid pyridine derivative (dPy), namely 4-acetylpyridine (4-Acpy) and 2-hydroxypyridine (2-OHpy), respectively.…”
Section: Introductionmentioning
confidence: 99%